2014
DOI: 10.1021/ja5031936
|View full text |Cite
|
Sign up to set email alerts
|

Determining the TiO2-Photocatalytic Aryl-Ring-Opening Mechanism in Aqueous Solution Using Oxygen-18 Labeled O2 and H2O

Abstract: The molecules O2 and H2O dominate the cleavage of aromatic sp(2) C-C bonds, a crucial step in the degradation of aromatic pollutants in aqueous TiO2 photocatalysis, but their precise roles in this process have remained elusive. This can be attributed to the complex oxidative species involved and to a lack of available models for reactions with a high yield of direct products. Here, we used oxygen-18 isotope labeled O2 and H2O to observe the aromatic ring-opening reaction of the model compound 3,5-di-tert-butyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…The kinetics of decoloration of the dyes may be described by a pseudo-first-order equation (Eqs. (1) and (2)):…”
Section: Methodsmentioning
confidence: 99%
“…The kinetics of decoloration of the dyes may be described by a pseudo-first-order equation (Eqs. (1) and (2)):…”
Section: Methodsmentioning
confidence: 99%
“…Among these photocatalysts, TiO 2 is one of the best because of its nontoxicity, acceptable stability and high photocatalytic activity. However, TiO 2 is responsive only to UV light, which accounts for no more than 4% of the solar spectrum, greatly limiting its photocatalytic efficiency and practical applications . Developing a novel photocatalyst with efficient visible‐light absorption and excellent stability remains a great challenge.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that molecular oxygen is the ultimate ring-opening agent of 3,5-di-tert-butylcatechol in TiO 2 photocatalysis using water/acetonitrile mixed solvent [6]. However, the photodegradation of 3,4-dihydroxybenzoic acid observed in the absence of oxygen as can be seen from .…”
Section: Effects Of Oxygen On Photodegradationmentioning
confidence: 89%
“…Catechol and its derivatives are important intermediates in the photo-degradation of benzene and its derivatives because OH radicals attack the aromatic ring before the latter is cleaved [4,5]. The two hydroxyl groups of catechol and its derivatives lead to strong adsorption on TiO 2 , which may be a crucial factor for the cleavage of the aromatic ring [6]. Aliphatic carboxylic acids are subsequently formed after the opening of aromatic ring, which also bind to TiO 2 [7].…”
Section: Introductionmentioning
confidence: 99%